Kit Hand Made Berbahan Limbah untuk Meningkatkan Kompetensi Alat Optik - Yohanes Eko Nugroho (Universitas PGRI Semarang, 2018)
There are two problems that underlie the classroom action research. First, the learning process is still dominated by lectures method and less empowering environment to develop the lesson materials. As a result, student competence is still far from expectations. Based on preliminary observations, in terms of daily test results VIII C grade on the subject matter “reflection and refraction of light”, indicating learning outcomes are still low. Classical completeness only reached 33.33% is still far from the minimum limit is 75%, and the average value of daily tests only 66.85, it is still far minimum completeness criteria is 75.00. While looking at the aspect of the achievement of scientific character, especially creativity, the majority of students are still far from the creative criteria. The qualitative value of creativity is considered good only 37.04%and 18.52% categorized quite creative. The remaining 44.44% of students categorized as less creative. Second, the quantity of waste every day are increasing the rate of production and consumption patterns. Such concerns foster ideas to make KIT Hand Madebased waste, such as milk cans, plastic bottles, syringes printer ink, plastic straws, plastic pipes, and others. Classroom action research carried out in three cycles. Cycle III, students who demonstrate creativity with a good reach 88.89%. Classical learning completeness reached 81.48% with an average value of 79.07. The science competence have increased significantly.